Plantas, pessoas e quintais : etnoecologia na área urbana de Tangará da Serra, Mato Grosso, Brasil - Moreira, Rogério Pinto de Moura (2014)
Ethnobotany is the study targeted the existing mutual relationship between human populations and plants where we can direct studies from this perspective in different environments between these backyards. Ethnobotany is the science that is concerned with safeguarding both the knowledge of the local flora as the culture of the people in relation to plants. This field has been studied in all parts of the world, including Brazil, with the most diverse areas of scientific knowledge in order to rescue the popular knowledge. Ethnobotany is part of the studies focused on a broader scale, the Ethnoecology, which somehow sets the study on human knowledge and local knowledge of the relations which exist between them, often involving processes occurring in the environment. Such studies are difficult to be applied, since they require an extensive knowledge of the language spoken by the population to be studied and how it relates to other aspects of culture. It encompasses a complex study that integrates the analysis present in komos corpus - praxis (kcp), these variables allow the perception and understanding of the environment and its natural processes. Thus, this study aims to conduct research of cultural and social ethnoknowledge residents of the city of Tangará da Serra, about traditional ecological knowledge we have about the use and management of plants present in their homes, based strongly linked to perceptions. The city of Tangará da Serra is located in the Southwest region of the state of Mato Grosso. The interviews were conducted in three districts of the municipality (Vila Portuguesa, Jardim Shangri-lá e Jardim São Luiz). Information from their backyards and locals were obtained through interviews with the use of forms with open and semi-structured questions. For data collection technique type Snow Ball ( snowball ) , and the intent, which was used for the selection of new informants to be incorporated in the interviews , which were recorded in the field notebook and recorded was applied when and the sample allowed species were photographed ( authorized ) for further analysis and identification. 54 residents living in the urban area were interviewed, and the age of the respondents ranged from 18 to 89 years old, and 85 % of respondents were women. During visits to backyards studied were found and identified 154 plant species distributed in 66 families. Plants with greater representation include the families Lamiaceae ( 12 species ), Asteraceae ( 9 species ), Rutaceae ( 9 species) and Solanaceae ( 6 species ) . In their backyards perceives a diversity of use of plant highlighting here six categories identified by the use of informants, medical, food, ornamental, toxic, personal beauty and mystique. In this study, the plant part most used in the preparation of home remedies was the sheet (71 nominations), followed by fruit (48 nominations) . The use of plants and their various applications in general are quite significant among the population of Tangará da Serra. The residents of this region proved to be aware of the importance of values , care and conservation of the natural resources in their backyards and in this scenario was evident a strong approach / interaction between human- plant relationships that they provide good quality of life , safety food and care , under the constructive optic their backyards .